Teachers’ Perceptions on the Content of When English Rings a Bell Textbook - Kiki Ramadhani; Siti Sarah Fitriani; Burhansyah Burhansyah (Universitas Syiah Kuala, 2017)
Textbook is a learning material that is often used by teachers in classroom. Textbook is needed by both students and teachers, either as a reference or as guidance during the teaching and learning process. The aim of this study was to describe the perception of English teachers of SMPN 2 Banda Aceh related to the content of English textbook “When English Rings a Bell” based on BSNP (Badan Standar Nasional Pendidikan) (2011) assessment aspects, namely the aspect of content feasibility. It was conducted to English teachers of the seventh grade students of SMPN 2 Banda Aceh. Two teachers were chosen as the interviewees of this study. A descriptive qualitative was used as the method in this study and the data was obtained by interviewing both English teachers. The results of interview with the two teachers about their perceptions about the textbook show that in terms of the suitability of material description with standard and basic competence, the content of “When English Rings a Bell” textbook is already complete and relevant with the 2013 curriculum, syllabus, and standard and basic competence. Furthermore, it shows that the materials provided in this textbook were well-organized and contained no ambiguity. However, according to the two respondents, “When English Rings a Bell” textbook still has some weak points which need to be revisited. For example, the materials are provided in general way with a few examples. Some negatives and positives perceptions regarding the content of the textbook were also found in this study.